Stress among health personnel at sub-district health promoting hospital Pathum Thani Province during COVID-19 outbreak - Rueangsaeng, Sakunrat; Prasertchai, Araya; Thammakun, Theerawut (Journal of Medical and Public Health Region 4, 2025)
This cross-sectional design survey research aimed to examine the relationships among personal factors, work-related factors, and stress in public health officials at Subdistrict Health Promoting Hospitals in Pathum Thani province during the COVID-19 outbreak. A total sample of 252 public health officials was recruited. Data were collected using a questionnaire developed by the researcher. A statistical analysis was conducted to determine frequencies, percentages, and averages. The inferential statistics using Chi-square test and Pearson's product moment correlation coefficients were calculated for examining the relationships at p-value of 0.05. The study results revealed that: (1) most of samples were females (83.3%), 50.4% aged 21-30 years, 54.8% were single, 90.5% completed a bachelor’s degree, 67.5% had 1-10 years working experience, and 45.2% had a monthly income of 15,001-20,000 baht; (2) their total work-related factors scored at a moderate level, 52.8% of them reported a moderate level of stress, work-related factors associated with work stress consisted of job characteristics and workload, success and career advancement, organizational structure and atmosphere, and relationships in the workplace, and organizational roles; and (3) personal factors related to stress included age, educational level, working time period, and monthly income. Suggestions: The executives should give importance on work-related factors by analyzing job characteristics and workload, evaluating work assignments that suit the abilities of official staff appropriately, and providing a support for professional advancement as to reduce a work stress during the public health emergency from pandemic.